Synthesis of MoVTeNb oxide catalysts for propane oxidation to acrylic acid via microwave irradiation-assisted slurry method - Muda, Ahmad Afandi (2014)
MoVTeNb mixed metal oxide catalyst has attracted great attention due to its ability to selectively oxidise propane to acrylic acid. In this work, the physicochemical properties of Mo1V0.3Te0.23Nb0.13 oxide catalysts synthesized via slurry method assisted with microwave irradiation were obtained. The catalysts were prepared in different pH of 1.19, 1.80, 2.67 and 3.20. The resulting precursors were calcined in air at 553 K for 1 hour followed by in nitrogen at 873 K for 2 hours. The catalysts were also post-treated through washing with hydrogen peroxide. All of the solids obtained were characterized by X-ray Diffraction (XRD), BET surface area measurement (SBET), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Temperature Programmed Reduction in hydrogen (H2–TPR), Transmission Electron Microscope (TEM) and Induced Couple Plasma-Atomic Emission Spectroscopy (ICP-AES). XRD results of the calcined samples displayed the formation of mixed orthorhombic M1 and hexagonal M2 phases. However, when washed with hydrogen peroxide, the hexagonal M2 phase was eliminated and only orthorhombic M1 phase was found. The removal of hexagonal phase contributes to the improved SBET values up to four times from its original value for each sample. H2-TPR profiles revealed higher amount of removable lattice oxygen for after washed with H2O2 catalysts. TEM analysis found that the washed MoVTeNbOx catalyst showed rod structure which was in line with the observed morphology in SEM. ICP-AES analysis for washed catalysts revealed that the composition of Te less than that of the theoretical value. Catalytic test showed that the catalysts achieved up to 25 % propane selectivity towards acrylic acid with propane conversion reached up to 38 %.